HACCP plan as a part of the food safety management system in the production of fermented milk products - Savanović, Danica; Novaković, Brane; Močević, Danijela (Journal of Engineering & Processing Management, 2017)
In this paper the authors have developed and implemented a HACCP plan for the production process of fermented milk products, as exemplified in the yogurt sample. Hazard analysis included 241 hazard, of which 99 hazard can be eliminated and prevented their occurrence, by taking timely preventive measures. The HACCP system is necessary to apply for the removal of all 11 identified hazards. In the present model, the five CCP were identified, three of them for biological and one chemical and one physical hazards. During many years of practical application, developed HACCP system has demonstrated some application advantages in relation to other systems for ensuring food safety, such as: efficiency, simplicity and low cost applications.